Targeting PNPO to suppress tumor growth via inhibiting autophagic flux and to reverse paclitaxel resistance in ovarian cancer - Xin Li; Wencai Guan; Huiqiang Liu; Jia Yuan; Fanchen Wang; Bin Guan; Junyu Chen; Qi Lu; Lingyun Zhang; Guoxiong Xu (Apoptosis, 2024)
Our previous study showed that pyridoxine 5’-phosphate oxidase (PNPO) is a tissue biomarker of ovarian cancer (OC) and has a prognostic implication but detailed mechanisms remain unclear. The current study focused on PNPO-regulated lysosome/autophagy-mediated cellular processes and the potential role of PNPO in chemoresistance. We found that PNPO was overexpressed in OC cells and was a prognostic factor in OC patients. PNPO significantly promoted cell proliferation via the regulation of cyclin B1 and phosphorylated CDK1 and shortened the G2M phase in a cell cycle. Overexpressed PNPO enhanced the biogenesis and perinuclear distribution of lysosomes, promoting the degradation of autophagosomes and boosting the autophagic flux. Further, an autolysosome marker LAMP2 was upregulated in OC cells. Silencing LAMP2 suppressed cell growth and induced cell apoptosis. LAMP2-siRNA blocked PNPO action in OC cells, indicating that the function of PNPO on cellular processes was mediated by LAMP2. These data suggest the existence of the PNPO-LAMP2 axis. Moreover, silencing PNPO suppressed xenographic tumor formation. Chloroquine counteracted the promotion effect of PNPO on autophagic flux and inhibited OC cell survival, facilitating the inhibitory effect of PNPO-shRNA on tumor growth in vivo. Finally, PNPO was overexpressed in paclitaxel-resistant OC cells. PNPO-siRNA enhanced paclitaxel sensitivity in vitro and in vivo. In conclusion, PNPO has a regulatory effect on lysosomal biogenesis that in turn promotes autophagic flux, leading to OC cell proliferation, and tumor formation, and is a paclitaxel-resistant factor. These data imply a potential application by targeting PNPO to suppress tumor growth and reverse PTX resistance in OC.